Implementasi Integrated Marketing Communication (IMC) Pada Public Relations PT Dream Tours and Travel Dalam Mempertahankan Pelanggan - Debby, Putri; Purnamasari, Oktaviana; El Adawiyah, Sa’diyah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The goal of this study is to investigate how Dream Tours and Travel LTD utilizes Integrated Marketing Communication (IMC) to keep customers coming back. The research approach taken is descriptive and qualitative, with participants including management from Dream Tours and Travel LTD and Umrah pilgrims. Information was gathered through interviews, observations, and documentation, and then analyzed using qualitative methods. The findings revealed that Dream Tours and Travel LTD has successfully executed an IMC strategy by utilizing a range of communication channels that work together seamlessly. The company utilizes customer data to present relevant offers, develops informative content to build trust, and conducts analysis to adjust their communication strategy. The strategic and tactical implementation of IMC has contributed to increased customer engagement and strengthened brand loyalty. In conclusion, Dream Tours and Travel LTD's implementation of IMC has been successful in retaining customers and can serve as a model for other companies in the same industry.